Effect of environmental factors in the decolorization of remazol brilliant blue R by polyporus sp. S133 - Hadibarata, Tony (2012)
The effects of environmental conditions such as pH, agitation, carbon and nitrogen sources, metal ion, salinity and phenolic compound on the decolorization of the anthraquinone type textile dyestuff Remazol Brilliant Blue R by white rot fungi, Polyporus sp. S133 were investigated. After extensive testing, the best performance took place at pH 4 and decolorization of the dye in liquid effluents was significantly increased by agitation. Compared to other carbon and nitrogen sources tested, glucose and ammonium tartrate gave rise to better decolorization performances. Decolorization of RBBR occurred in the presence of metal ions which are typically found in textile industry effluents. Of all the metal ions tested, Fe ++ was the most inhibiting of the decolorization. The effect of culture salinity on decolorization was also investigated. Under high-salt conditions, RBBR was also decolorized completely in 6 d. The presence of phenolic compounds inhibited the decolorization at a concentration of 1 mM, but protocatechuic acid showed no inhibition. The results indicate that possibly anthraquinone type dyes such as RBBR act as enzyme substrates that are directly oxidized by laccase.